2012
DOI: 10.3892/mmr.2012.1239
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effects of Actinidia polygama extract in mice with high-fat diet-induced obesity

Abstract: Abstract. Actinidia polygama has been used as a herbal folk medicine for treating pain, gout, rheumatoid arthritis and inflammation. In the present study, the anti-obesity properties of Actinidia polygama extract (APE) were investigated in mice with high-fat diet-induced obesity. APE treatment of high-fat diet (HFD)-fed obese mice significantly reduced body weight, adipose tissue mass and serum triglyceride and leptin levels relative to the HFD-fed mice. Food intake did not differ between the HFD and HFD+APE g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…However, adipocyte accumulation in adipose tissue may cause obesity and related complications. Recent studies demonstrated that long-term HFD increases in serum TG, FFA, glucose, TC, HDL, and LDL decrease cholesterol levels, leading to an imbalance in serum lipid composition (24,34,35). This imbalance is considered as the main risk factor for several diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, adipocyte accumulation in adipose tissue may cause obesity and related complications. Recent studies demonstrated that long-term HFD increases in serum TG, FFA, glucose, TC, HDL, and LDL decrease cholesterol levels, leading to an imbalance in serum lipid composition (24,34,35). This imbalance is considered as the main risk factor for several diseases.…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, obesity is characterized by an increase in the size (hypertrophy) and number (hyperplasia) of adipoctyes. Hence, a complete understanding of the mechanisms regulating adipogenesis is essential and of utmost priority ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of herbal products have been reported to exert beneficial effects against obesity and anti-inflammation in both animal and human subjects; nevertheless, few studies have systemically assessed the relationship between herbal medicine and gut flora in an obesity/endotoxemia model in detail [17][19].…”
Section: Introductionmentioning
confidence: 99%